Penerapan Model Pelatihan Berbasis SMART dalam Layanan Konsultasi untuk Kemampuan Guru BK Melaksanakan Layanan Khusus - Laia, Asa’aro; Telaumbanua, Nurhayati; Laia, Sri Wahyuni (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2021)
The teachers complained that the training that had been going on at P4TK for a week or more, and was only filled with theories that they had previously stated, while at the end, some teachers were tired and when they returned to their assignments they only brought a sheet of research. This program aims to provide training to participants in a short time in one skill training. This training uses a SMART model approach (specific, measurable, achievable, relevant, and time-bound) with the material